Research of Using Games in Physics Education - Horváthová, Jana; Haverlíková, Viera (Scientia in educatione, 2020)
The article presents results of research focused on using games as a physics teaching method and identifying factors influencing using or not using games by teachers of lower and upper secondary schools. Attitudes of teachers who claim to be using games in teaching physics are compared to those who do not use them. Results of the research can be used in further development of didactic games that will reflect teachers‘ needs, expectations and fears in order to enable broader and more effective use of games in science education.